SCREENCAST AND ITS EFFECT ON IMPROVING LEARNERS’ ACADEMIC ACHIEVEMENT AND MOTIVATION IN PHYSICS - Brenda Lyn Amanda Basas Orocio; Joji Davila Linaugo (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2023)
Screencasts are multimedia-based learning which involves multimodal sensory, such as eyes and ears. These are increasingly used as schools transition to blended learning mode. This study aims to describe the screencast and its effect on improving learners’ academic achievement and motivation in Physics. This quasi-experimental research determined learners’ academic achievement and level of motivation before and after treatment to screencasts focusing on heat, temperature, and electricity. The study was done in a large public secondary school in a highly urbanized city in the central Philippines. Academic achievement was measured through a constructed test while the level of motivation was evaluated using Keller’s Instructional Materials Motivation Survey. Results showed that screencasts improved the learners’ academic achievement and increased their level of motivation. The use of screencast has a good impact on changing learners' knowledge and skills and is an effective online learning media. Findings also obtained a p-value of 0.00 which showed that there is a significant difference in the learner’s academic achievement before and after treatment to screencast. This study discovered that learning using screencasts is engaging to the learners. The screencast provided the learners with the opportunity to learn at their pace and brought them better learning experiences.